Intradiploic meningioma mimicking calvarial metastasis: Case report [Kalvarial metastazi̇ taklit eden i̇ntradiploik meningioma: Olgu sunumu] - (:unkn) unknown (Turkish Neurosurgical Society, 2009)
Meningiomas are the most common benign intracranial neoplasms. Nearly 20% of all primary intracranial tumors are meningiomas. Primary intraosseous meningiomas are a subtype of the meningiomas that represents the most uncommon manifestation of meningiomas. Although rare, these tumors can be found to occur in unexpected areas of the head and neck. The patient was a 78- year-old male who was operated two times for urinary bladder cancer. During his routine oncology follow-ups, the PET scan demonstrated a hyperactive area in the right parietal bone. Preoperative diagnosis was a metastasis, but histological examination revealed an osteolytic interosseous meningioma. The possibility of an intraosseous meningioma mimicking a metastatic tumor should be kept in mind.
Keywords: İntradiploic; Meningioma; Metastasis; Skull